Perbandingan Efektivitas Lama Waktu Suction Pada Pasien Yang Terpasang Endotrakeal Tube Terhadap Saturasi Oksigen Pada Pasien di Ruang Operasi - Naufal Annasy; Ika Kusuma Wardani; Aresta Rahma Mutaqina (Calory Journal Medical Laboratory Journal, 2024)
Background : endotracheal tube suction is an intervention that is often performed by nurses to help with airway patency. Patients who have an endotracheal tube installed allow the accumulation of secretions so that suction is carried out with duration of 10 seconds and 15 seconds. Purpose : the study was to determine the effectiveness of increasing oxygen saturation values before and after suctioning for 10 seconds and 15 second in patients with endotracheal tubes. Methods : the research method for type of research uses a quasi-experimental research design using a pre-test and post-test with group design. The number of respondents in this study were 30 people. Oxygen saturation values were measured using and data analysis using univariate and bivariate analysis was perfomed to determine the frequency distribution of the characteristics of the respondents while bivariate analysis used the Shapiro wilk test. Result : there was no significant difference in the group with a suction time of 10 seconds and 15 seconds in patient with a suction time of 10 seconds in the value of oxygen saturation with p value (p>0.05)=0.059. Recommendation : long suction time of 10 seconds can increase the saturation value oxygen